Strategic Pathways to Educational Excellence: An ISM Analysis of Leadership, Curriculum, and Service Quality in Muhammadiyah Schools Amid Society 5.0 - Muhammad Samsudin; Ratna Sari; Casnan; Azis Ilham Hanafi (Universitas Muhammadiyah Surakarta, 2025)
This research aims to analyze the determining factors of Muhammadiyah school management excellence in Society 5.0 using the Interpretive Structural Modeling (ISM) approach. School excellence is an important factor in maintaining competitiveness and improving the quality of education. To achieve school excellence, it is important to understand the factors that influence school excellence. The method used in this study is qualitative descriptive with the Interpretive Structural Modeling (ISM) approach, a system analysis method based on a conceptual framework to determine priority choices and connect important factors in a complex system of society 5.0 to create inclusive and sustainable schools. The key factors determining the excellence of Muhammadiyah schools based on the results of the ISM analysis are Principal Leadership, Quality of Teachers and Education Personnel, School Services, and Learning Curriculum. The key factor determining school excellence will support quality school management, thereby producing quality graduates.